Examples of Hadiths with Illusion in Sunan Abi Dawood - Abd , Maysir (Islamic Sciences Journal, 2023)
These few pages are knowledge about the illusion and are not absorbed, and each narrator who described the illusion needs a special study for it, the researcher collects the sayings of the scholars and those who described it as an illusion and the reason for describing it as an illusion and the hadiths they deluded with, then compares and sees whether there is a follower or not, after all of that he can He reaches an understanding of the reality of each narrator. By Allah, I ask that this article be of benefit to the honorable reader, and that if I am right, then by the grace of Allah and thanks to the scholars of hadith, and if I am wrong, it is from myself.